Hubungan Tingkat Pengetahuan dengan Pengendalian Tekanan Darah pada Hipertensi di Puskesmas Garuda Bandung Tahun 2020 - Muhammad Deri Ramadhan (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2020)
Background: Hypertension is a condition in which a person has an increase in blood pressure above normal as indicated by a systolic number of more than 140 mmHg and a diastolic number of more than 90 mmHg. Factors that influence hypertension are the level of knowledge and blood pressure control. Objective: To determine the relationship between the level of knowledge and control of blood pressure in hypertension at Garuda Bandung Health Center. Methods: This study design used a cross section with 52 respondents. The sampling technique was purposive sampling. The research instrument used a questionnaire. Univariate and bivariate analysis with frequency distribution and bivariate withtest Chi Square. Results: There is a relationship between the level of knowledge and blood pressure control in hypertension with a value of p = 0.001 , thus p < (0.01 <0.05). Conclusion: There is a significant relationship between knowledge level and blood pressure control in hypertension (p = 0.001).